Wastewater Treatment for African Catfish (Clarias gariepinus) Culture by Using Anaerobic Process - Darwin Darwin; Sarbaini Sarbaini; Satria Purwanto; Fatwa Dhiauddin; Muhammad Ilham; Afrizal Fazil (agriTECH, 2017)
This study aimed to set up an anaerobic treatment system for the treatment of wastewater derived from the farming of African Catfish (Clarias gariepinus). In this current study, anaerobic treatment of wastewater derived from the African catfish (Clarias gariepinus) aquaculture was conducted in semi-continuous reactor as well as batch reactor under mesophilic condition at 35 °C. The results revealed that the semi-continuous reactors generated higher biogas yield (69.27 mL/g VS) compared with batch reactor (22.81 mL/g VS). High conversion rate of anaerobic treatment process operated in semi-continuous reactor was also represented in higher percentage of COD removal (82.6%) compared with batch reactor which was only 62.76%. After conducting anaerobic treatment process on the wastewater derived from the catfish aquaculture, some parameters including total dissolved solids (TDS), Phosphorous (P), potassium (K) and electrical conductivity (Ec) increased in both batch and semi-continuous reactors. Batch reactors showed TS, VS and COD reduced from 0.23%, 42.88% and 1440 mg/L to 0.137 ± 0.024%, 22.78 ± 19.44% and 536.32 ± 11.27 mg/L, respectively. The results obtained from semi-continuous reactor revealed that TS, VS and COD reduced from 0.23%, 42.88% and 1440 mg/L to 0.219%, 24.353% and 250.61 mg/L, respectively. This study is highly significant for the environmental protection system.